'A man drives as he lives'? Taxi drivers accounts of urban road (anti) citizenship - Ncube, Vuyolwethu Lulama Gugulethu (My University, 2019)
Taxi drivers play a key role in the everyday lives of South Africans, providing transport to over 65% of the population. This study explored how taxi drivers perceive their world(s) through the theoretical lens of citizenship. The aim of this study was to explore the taxi drivers’ experiences on and off the road and understand how they account for their behaviour and driving patterns. Ten taxi drivers were interviewed in Johannesburg. Vignette-initiated semi-structured interviews constituted the research instrument. The data obtained was analysed using Interpretive Phenomenological Analysis (IPA). The data corpus yielded one overarching theme, three subthemes with two ancillary subthemes each. The main finding of the study was that there exists a specific type of citizenship that is expressed on the roads; road citizenship. This notion suggests that citizenship on the roads is not a static state but rather a complex, situation-specific phenomenon that is reported to be experienced in varying ways across different groups of people in a range of contexts. The road was found to be a site that can be interacted with and understood as a unit of analysis in and of itself. The findings of this study are invaluable to other road users, policy makers and stakeholders in the transport sector. The results present a necessity to employ multimodal investigations that address the context and the road users’ experiences on and off the road. This enables insight into multiple viewpoints of accounts of driving behaviour and ultimately presents a more comprehensive knowledgebase on which to tailor-make traffic and road interventions.
A research report submitted to the Faculty of Humanities, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree Master of Arts in Social and Psychological Research, 2019